Study of mineral fouling mitigation on heat exchanger surface - Kazi, S.N.; Teng, K.H.; Zakaria, M.S.; Sadeghinezhad, E.; Bakar, M.A. (Elsevier, 2015)
Investigation on fouling behaviour of calcium carbonate on heat exchanger surfaces as well as mitigation of fouling are presented in this paper. By varying parameters such as concentration of the fouling solution, temperature of the heating surface, type of materials and use of additives, the fouling rate on the test specimens were observed. A set of experiments were performed by using calcium carbonate solution. Fouling rate, fouling resistances and the rate of heat transfers were determined for different heat exchanger material surfaces. Fouling resistance is enhanced by the thermal conductivity and temperature of the heat exchanging surfaces and also by the concentration of the foulant in the solution. The addition of gum arabic additive (benign to the environment) to the solution retarded the rate of deposition. The results of these investigations could be design aid for economic and enhancement of heat exchanger performance. (C) 2015 Elsevier B.V. All rights reserved.